Selection of Priority Sequence of Investor's Portfolio with the Use of the Supply Chain Management in the Criteria of "Against Nature" Game - M.A Gorskiy; M.A Khalikov; A.Yu Kukharenko (International Journal of Supply Chain Management, 2019)
As part of the research related to the improvement of the portfolio theory of H. Markowitz, J. Tobin, and W. Sharpe for use in established as well as developing modern stock markets, the authors proposed a concept and a numerical algorithm to choose the priority sequence of financial portfolios of non-institutional investors, taking into account their preferences and projected changes in the parameters included in financial portfolios assets. In the absence of an optimization model suited to the market, an investorâ€™s ability to choose a portfolio from several alternatives that satisfy the preferences in terms of profitability, risk, and liquidity significantly improves the quality of an investment decision by employing supply chain strategy. The authorsâ€™ concept provides for the formation of a set of alternative financial portfolios with different characteristics in a priori given quantity: the selection of an integral quality indicator of the investment portfolio, the formation of the priority sequence of portfolios using the game theory method â€œagainst natureâ€, and the synthetic â€œgameâ€ Wald-Savage criterion, which allows the consideration of the investorâ€™s predisposition for riskâ€“return pair. A comparative analysis of investment decisions based on the â€œclassicalâ€ portfolio theory and the authorâ€™s concept allowed the conclusion that the proposed approach and the numerical method are correct and are better in comparison to traditional methods and efficiency algorithms when applied to the portfolio investment tasks.